(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The impact of employing wheat straw ash as a partial substitute material for cement in concrete mining is presented in this research. Wheat straw ash is the residue left over after open burning wheat straw. The appropriateness of wheat straw ash obtained from uncontrolled burning of wheat straw as a partial replacement for cement in concrete is investigated in this study. The compressive strength and workability of concrete blended wheat straw ash cement are examined and investigated by substituting cement by 15%, 20%, 25%, and 30% by weight to OPC. Slump tests were performed on new concrete, and compressive strength tests were performed on hardened concrete. Several cubes were evaluated after 7 and 28 days. The results demonstrate that wheat straw ash is a decent replacement material. The slump value dropped as wheat straw ash increased. The compressive strength decreased as WSA increased.